Does sadness bring myopia: an intertemporal choice experiment with college students - Lei, Peng; Zhang, Hao; Zheng, Wenyu; Zhang, Luoyi (Frontiers in Psychology, 2024)
While economics often interprets individual intertemporal choice preferences through the rationality assumption of utility maximization, the reality is that as emotional beings, individuals' preferences for intertemporal behavior are much more diverse and inconsistent. Prior research has predominantly focused on positive or negative emotions based on prospect theory, such as anxiety, anger, disgust, and depression. However, there has been relatively little research on how sadness affects individuals' preferences for immediate and future rewards. In this study, 170 college students are recruited as participants, and their emotions are primed with a video before engaging in an intertemporal task. Covariance analysis and logit regression model are established to examine the main and interactive effects of sadness on individuals' immediate reward preferences. The findings reveal that sadness led individuals to prefer smaller immediate rewards, demonstrating a more myopic behavioral pattern, but didn’t affect time discount rate. As the reward baseline increases, sadness’s impact on immediate reward preferences is more pronounced, exacerbating individuals' myopic behavior. In conclusion, this research provides a better understanding of the main effect of sadness on individuals' intertemporal choice behavior and sheds light on the counterintuitive moderating effect of increased baseline amounts.